2023
DOI: 10.1186/s12893-023-01953-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of pancreatitis after endoscopic retrograde cholangiopancreatography in patients with biliary tract diseases

Abstract: Background To investigate the risk factors of pancreatitis after endoscopic retrograde cholangiopancreatography (ERCP) in patients with biliary tract diseases. Methods We retrospectively analyzed the clinical data of 480 patients who underwent ERCP for biliary tract diseases at the Affiliated Zhongshan Hospital of Dalian University from October 2011 to October 2016. The patients were divided into a study group (n = 75, with PEP) and a control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…The study also found that the proportion of women, elevated blood amylase measured three hours after surgery, and the maximum diameter of larger stones were independent risk factors for PEP.Previous studies mostly con rmed women as risk factors for pancreatitis after ERCP, which is consistent with this study [24][25][26] .The increased risk of PEP in female patients may be attributed to gallstones and sphincter of Oddi dysfunction (SOD).In the present study, patients with elevated blood amylase measured three hours after surgery were more likely to develop PEP, consistent with the ndings of Ze-Hui Lv et al [27] .In addition, the diameter size of bile duct stones was also correlated with the occurrence of PEP.Patients with large stone diameter may lead to biliary obstruction, cholestasis and bile duct injury due to natural stone discharge di culties, stone-embedded, surgery and other factors, which are prone to secondary bacterial infection and increase the risk of PEP.…”
Section: Discussionsupporting
confidence: 90%
“…The study also found that the proportion of women, elevated blood amylase measured three hours after surgery, and the maximum diameter of larger stones were independent risk factors for PEP.Previous studies mostly con rmed women as risk factors for pancreatitis after ERCP, which is consistent with this study [24][25][26] .The increased risk of PEP in female patients may be attributed to gallstones and sphincter of Oddi dysfunction (SOD).In the present study, patients with elevated blood amylase measured three hours after surgery were more likely to develop PEP, consistent with the ndings of Ze-Hui Lv et al [27] .In addition, the diameter size of bile duct stones was also correlated with the occurrence of PEP.Patients with large stone diameter may lead to biliary obstruction, cholestasis and bile duct injury due to natural stone discharge di culties, stone-embedded, surgery and other factors, which are prone to secondary bacterial infection and increase the risk of PEP.…”
Section: Discussionsupporting
confidence: 90%
“…Female, the history of pancreatitis, difficult intubation and EST in this study are all risk factors for PEP, which have been reported in multiple studies [ 18 20 ]. Interestingly, we found that patients with HBP were more likely to develop PEP in this study.…”
Section: Discussionsupporting
confidence: 64%
“…To address these issues, the intraoperative collection of bile and bacterial culture samples can greatly improve the accuracy of diagnosis and treatment by providing a more comprehensive understanding of the patient’s condition ( Asukai et al, 2023 ; Papazyan et al, 2023 ). Moreover, although there are many methods to treat corresponding infectious complications, the effect is not satisfactory ( Chi et al, 2023 ). Therefore, it is necessary to actively prevent pathogen infection in patients, and important to understand the characteristics of pathogen infections and their associated risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Biliary infection in patients is common and has been associated with invasive clinical procedures, septicemia, intestinal barrier dysfunction, and gut bacteria translocation ( Chi et al, 2023 ; Ekpanyapong and Reddy, 2023 ). It continues to be a significant cause of severe complications and morbidity in patients, particularly in elderly patients with underlying comorbidities.…”
Section: Introductionmentioning
confidence: 99%